(untitled) (Web of Teachers: Inderscience Research, 2024)
The axiological approach is an important philosophical principle aimed at studying values and moral norms in pedagogy. This approach is aimed at shaping the moral and aesthetic values of youth and students in the educational process. Axiology is closely linked to the field of ethics and aesthetics in philosophy and aims to explain and teach the importance of goodness, justice, and spiritual values in education.